Automating YAML Encryption And Secure Access With Ephemeral Credentials - Vasikarla, Raman (Journal of International Crisis and Risk Communication Research, 2025)
Multi-cloud​‍​‌‍​‍‌​‍​‌‍​‍‌ infrastructure deployments are increasingly reliant on YAML-based configuration management for declarative system provisioning. Sensitive and private credentials that are embedded in configuration files make security a major concern when these files when stored as plaintext or managed through manual processes. Traditional secrets management techniques fail to address the dual challenges of configuration encryption and runtime access control simultaneously. The article presents an integrated framework combining automated YAML encryption with dynamic ephemeral credential generation to eliminate static credential exposure. Hierarchical encryption pipelines employ asymmetric cryptography to separate encryption responsibilities from decryption privileges while maintaining configuration readability. Validation mechanisms enforce cryptographic consistency across deployment environments through automated schema verification and encryption coverage analysis. Ephemeral credential systems implement vault-based dynamic secret generation where access tokens exist only during specific operational tasks. Role generators issue time-limited credentials bound to requesting identities with minimum required privileges. Integration with continuous deployment pipelines occurs through plugin architectures that intercept configuration files at multiple workflow stages. Cross-platform orchestration patterns facilitate the normalization of secret access that is compatible with different cloud environments through unified abstraction layers. The framework is a means of implementing Zero Trust concepts by, among other things, ensuring that there is continuous verification as well as microsegmentation through the use of granular access controls. The full observability integration also supports the recording of encryption operations, credential issuance events, and access patterns for compliance automation. The combined architecture demonstrates how cryptographic automation and dynamic credential management address fundamental weaknesses in contemporary Infrastructure as Code security practices.